2016
DOI: 10.1177/0958928716645076
|View full text |Cite
|
Sign up to set email alerts
|

User choice in Swedish eldercare – conditions for informed choice and enhanced service quality

Abstract: Proponents of user choice argue that this type of policy arrangement improves the quality of public social services since users are expected to select the most highly performing providers. In order for users to make informed choices, however, they need quality information about the services offered by different providers. In this article, we carry out a case study, investigating whether information about service quality was presented to users of home-based elderly care in Sweden. The analysis is based on uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
0
27
0
3
Order By: Relevance
“…Many users of home care services, within the Swedish Free Choice System, did not find the received information a sufficient basis for their choice of provider (Hjalmarsson & Norman, 2004;National Board of Health and Welfare, 2015). An analysis of the information from providers showed that it provided little guidance for users to make informed choices (Moberg, Blomqvist & Winblad, 2016). Many older people do not see the value of choosing between different, more or less anonymous, service providing agencies and very few change their initial choice of provider of eldercare (Edebalk & Svensson, 2010;National Board of Health and Welfare, 2015;Vamstad, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many users of home care services, within the Swedish Free Choice System, did not find the received information a sufficient basis for their choice of provider (Hjalmarsson & Norman, 2004;National Board of Health and Welfare, 2015). An analysis of the information from providers showed that it provided little guidance for users to make informed choices (Moberg, Blomqvist & Winblad, 2016). Many older people do not see the value of choosing between different, more or less anonymous, service providing agencies and very few change their initial choice of provider of eldercare (Edebalk & Svensson, 2010;National Board of Health and Welfare, 2015;Vamstad, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Personalization, choice, and control are key elements of adult social care in many countries (Moberg, Blomqvist, & Winblad, ). Operationalized through personal budgets (PBs) and direct payments (DPs) in England and other forms of cash for care payments internationally (Glendinning & Kemp, ; Ungerson & Yeandle, ), a fundamental assumption is that enabling people to manage the resources available to them will enhance their ability to access appropriate care and support, and tailor it to their needs.…”
Section: Introductionmentioning
confidence: 99%
“…Important to both quasi‐market and consumerist approaches is the availability and quality of information and the capacity to use that information (Dixon, Robertson, & Bal, ; Moberg et al, ). Glendinning () summarizes some of the issues facing social care service users in making choices, including issues specific to people likely to be self‐funders.…”
Section: Introductionmentioning
confidence: 99%
“…Second, Hypothesis 2, that the care-service evaluation indexes of 2013 and 2016 would separately affect the user satisfaction, was confirmed (30). According to the hierarchical regression analysis for 2013, education time, attire management, contract termination, document filing, etc., had an effect on user satisfaction.…”
Section: Discussionmentioning
confidence: 82%